Mixed Ligand Schiff Base Complexes of Some Metal (II) Salts: Preparation, Spectral Characterization and Antibacterial Screening - Faeza Hasan Ghanim (Journal of Global Pharma Technology, 2018)
Schiff base ligand (E)-2-((3-hydroxyphenylimno) methyl)-6-methoxyphenol has been synthesized from m-aminophenol and o-vanillin. The geometry of Schiff base has been determined on the basis of Micro elemental analysis (C.H.N), molar conductance. Mass,  1HNMR, FT-IR and UV-Vis spectroscopic techniques. Metal mixed ligand complexes for manganese(II),cobalt(II),nickel(II),copper(II),zinc(II) and cadmium(II) for Schiff base ligand and paracetemol have been prepared in the molar ratio 1:1:1 (M:L: Para), (M= Metal, (L)= Schiff base ligand and (Para) = paracetamol) have been prepared and identified by using flame atomic absorption, FT.IR and UV-Vis spectral methods, on other than magnetic properties and conductivity measurements. Their electrical conductance values indicate that all complexes are electrolytes. From   obtained data octahedral geometry were suggested with all prepared complexes. Schiff base ligand, paracetamol as well as metal (II) complexes were assayed by antibacterial activity against some pathogenic bacteria using disc diffusion method.Keywords: Schiff base, Paracetamol, Mixed ligand complexes, Antibacterial screening.